The Interaction of Social Media and Social Comparison Orientation in Shaping Financial Self-Efficacy of Millennials - Rahayu Oktaviani; Andika Pratama (PT PUSTAKA CENDEKIA GROUP, 2023)
This study aims to examine the influence of social media use and social comparative orientation on financial self-efficacy in the millennial generation in Medan City. In today's digital era, social media is the main source of information and interaction for the millennial generation, as well as a tendency to compare oneself with others which can affect confidence in managing personal finances. The research approach used was quantitative by collecting data through a Likert scale based questionnaire from 90 respondents selected by purposive sampling. Data analysis was carried out using the Partial Least Squares (PLS) method to test the relationship between variables. The results of the study show that the use of social media has a positive and significant effect on financial self-efficacy, which means that the more intense and effective the millennial generation uses social media to obtain financial information, the higher their confidence in managing finances. In addition, social comparison orientation also has a significant influence on financial self-efficacy with a complex nature; Social comparisons can motivate increased financial ability but can also lead to feelings of inferiority if done unhealthily. These findings suggest that social comparison orientation plays an important role in mediating the relationship between social media and financial self-efficacy. This research contributes to the understanding of how social media and the process of social comparison affect the financial confidence of the millennial generation. The practical implications of this research can be used as the basis for the development of financial education programs that emphasize the management of social media use and fostering a healthy social comparison attitude to improve the financial self-efficacy of the millennial generation in the digital era.